2018
DOI: 10.1080/02770903.2018.1463379
|View full text |Cite
|
Sign up to set email alerts
|

Association of secondhand smoke exposure with asthma symptoms, medication use, and healthcare utilization among asthmatic adolescents

Abstract: SHSe reduction efforts are needed for asthmatic adolescents, and EDs/UCs are promising venues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…Our main findings were that short-term SHS exposure did not result in any significant change in symptoms or noticeable change in medication usage, in 24 hours monitoring among patients with asthma and COPD, in contrast with prior results obtained 16 .…”
Section: Discussioncontrasting
confidence: 99%
“…Our main findings were that short-term SHS exposure did not result in any significant change in symptoms or noticeable change in medication usage, in 24 hours monitoring among patients with asthma and COPD, in contrast with prior results obtained 16 .…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent US national survey 23 , children with SHS exposure were 30% more likely to be diagnosed as having asthma than non-exposed children. When exposed to SHS for > 1 h for 7 days, asthmatic children showed an elevated risk of reporting symptoms such as wheezing, dry couth, and sleep disturbance 24 . In line with previous studies, our study revealed that SHS exposures at home, school, and public places are related to the highest odds of single allergic morbidity, which suggests that increased exposure sources may result in stronger association with symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of having Emergency department/urgent care visits was two times higher in asthmatic adolescents exposed to SHS compared with unexposed adolescents. The group of adolescents with asthma were also 1.5 times more likely to use a rescue medication, nebulizer treatment, or other controlling medication and over 3.5 times more likely to have had an asthma attack that required the use of an oral or injected CS [ 170 ]. A recent study found that SHS in children aggravated the severity of asthma by affecting the balance of Treg/Th17 cells with a higher percentage of Th17 cells, while the percentage of Treg cells was reduced.…”
Section: Indoor Air Pollutionmentioning
confidence: 99%